Trade in Tasks and the Organization of Firms - Dalia Marin; Jan Schymik; Alexander Tarasov (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
We incorporate trade in tasks à la Grossman and Rossi-Hansberg (2008) into a small open economy version of the theory of firm organization of Marin and Verdier (2012) to examine how offshoring affects the way firms organize. We show that the offshoring of production tasks leads firms to reorganize with a more decentralized management, improving the competitiveness of the offshoring firms. We show further that the offshoring of managerial tasks relaxes the constraint on managers but toughens competition, and thus has an ambiguous impact on the level of decentralized management and CEO wages of the offshoring firms. In sufficiently open economies, however, managerial offshoring unambiguously leads to more decentralized management and to larger CEO wages. We test the predictions of the model based on original firm level data we designed and collected of 660 Austrian and German multinational firms with 2200 subsidiaries in Eastern Europe. We find that offshoring firms are 33.4% more decentralized than non-offshoring firms. We find further that the average fraction of managers offshored reduces the level of decentralized management by 3.1%, but increases the level of decentralized management by 4% in industries with a level of openness above the 25th percentile of the openness distribution. Lastly, we find that one additional offshored manager lowers CEO wages relative to workers by 4.9%.
urn:nbn:de:bvb:19-epub-21741-9
Keywords: F12; F14; L22; D23; 330; international trade with endogenous organizations; the rise of human capital; theory of the firm; multinational firms; CEO pay